Applications of Metal Organic Frameworks in Wastewater Treatment: A Review on Adsorption and Photodegradation - Russo, Vincenzo; Hmoudah, Maryam; Broccoli, Francesco; Iesce, Maria Rosaria; Jung, Ok-Sang; Di Serio, Martino (Frontiers in Chemical Engineering, 2020)
The growing accumulation of emerging contaminants in the environment can cause direct and indirect water pollution that puts human lives at risk. The fact that these contaminants are not or cannot be eliminated from the municipal water utilities, poses a significant concern. Researchers are currently pulling massive attention to improve existing technologies, develop new strategies and provide environmentally and durable solutions to mitigate water contamination problems. Adsorption and photodegradation are two of the most sustainable technologies that are used in water purification. These technologies have many advantages because of the economic, simple and easily operated designs needed to treat wastewater. Within these applications, metal organic frameworks (MOFs) are playing a significant role as novel class of porous materials characterized by a crystalline structure. MOFs are considered good candidates to be employed in wastewater treatment technologies because of the tunability of their features. The scope of this review article is to provide a comprehensive description of the recent studies published in the literature about the adsorptive and photocatalytic use of MOFs for the removal of organic emerging contaminants from wastewater. Furthermore, this study briefly highlights the synthesis technologies of MOFs. Finally, future perspective, and challenges associated with MOFs large scale production are discussed.